Eṭi jīẏā kāhinī : Śrīpūrṇacandra Bharālīra bicitra abhijñatā - Goswami, Praphulladatta, 1919- (Bhinaṭeja Bukaśvapa, 1979)
On the life of Pūrṇacandra Bharālī, 1907-1978, Assamese business entrepreneur.